Prevalence of malocclusion among 15-year-old school children using dental aesthetic index in Nalgonda district, Andhra Pradesh, India: A cross-sectional study - B R Chandra Shekar; S Suma; Sudarshan Kumar; Jagadeeswara Rao Sukhabogi; B C Manjunath (Wolters Kluwer Medknow Publications, 2014)
Background: The available literature on the prevalence of malocclusion among school children in endemic fluoride areas in India is scanty. Objectives: The objective was to assess the prevalence of malocclusion using dental aesthetic index (DAI) and its association with gender, area of residence, and fluoride concentration among 15-year-old school children. Materials and Methods: This cross-sectional study was conducted among 15-year-old school children in the rural and urban areas of Nalgonda district, Andhra Pradesh, India. Two-stage cluster sampling was used for selecting the eligible children. Six out of 59 mandals in Nalgonda district were selected by simple random sampling technique. All the secondary schools in rural and urban areas of these mandals were listed and subsequently, four schools from each of these mandals were selected using random sampling. All eligible children aged 15 years were selected and assessed for malocclusion using Dentofacial anomalies with criteria of DAI by three trained and calibrated dentists. The DAI in relation to gender and area of residence were compared and analyzed using SPSS 16. Student's t-test and one-way ANOVA were used for comparing the mean values between groups. The qualitative data were analyzed using the Chi-square test. Results: A total of 1484 children was examined. The prevalence of malocclusion was 17.9%. The prevalence was significantly higher (P = 0.001) among females (23.6%) compared to males (13%). The prevalence was significantly higher (P = 0.001) in urban areas (22.2%) compared to rural areas (15%). The prevalence was significantly less (P = 0.001) in optimal (13%) and above optimal areas (8%) compared to below optimal areas (23%). Conclusion: The prevalence and severity of malocclusion were more among females, urban, and below optimal fluoride areas.